Perspectives on Precision Medicine in a Tribally Managed Primary Care Setting. Issue 4 (16th September 2020) - Beans, Julie A.; Woodbury, R. Brian; Wark, Kyle A.; Hiratsuka, Vanessa Y.; Spicer, Paul
Abstract: Background: Precision medicine (PM) research and clinical application is moving forward at a rapid pace. To ensure ethical inclusion of all populations in PM, in-depth understanding of diverse communities' views of PM research and PM implementation is necessary. Methods: Semi-structured interviews were conducted to explore perspectives on PM in a tribally managed healthcare organization. Thematic analysis was used to analyze data from 46 interviews. Results: Participants described gains in diagnostic efficiency, risk identification for preventable disease, and the advancement of population-specific biomedical research as key benefits of PM. Concerns expressed related to privacy risks associated with data-sharing, overpromising on PM, and managing patient expectations related to PM. Stakeholders encouraged PM implementation to be preceded by health education activities that leverage a range of communication strategies. Conclusion: Perspectives described in this study may aid in and should be considered prior to implementation of PM in this and other healthcare systems, especially those serving diverse populations.